Exodus. Rezeptionen in deuterokanonischer und frühjüdischer Literatur - Gärtner, Judith (Deuterocanonical and Cognate Literature Studies, 2016)
The story of Exodus from Egypt is a key founding myth that informs Israel`s collective identity and pervades all of Old Testament literature. In the Hellenistic period, the Exodus story enjoyed a renaissance, and it continues to influence literature to this day. This anthology provides the first comprehensive overview of the reception of Exodus in various contexts.